“Sharing is my only option”: an ethnographic analysis of the underlying contexts of needle and syringe sharing among people who inject drugs using the socio-ecological framework - Khan, Mohammad Niaz Morshed; Irfan, Samira Dishti; Hossain, Md. Alamgir; Moriyama, Michiko; Khan, Sharful Islam (Frontiers in Public Health, 2025)
BackgroundPeople who inject drugs (PWID) in Bangladesh are part of a long-standing needle syringe program, which faced challenges in containing the spread of HIV, thus warranting exploration of the drivers of needle and syringe sharing. This article aimed to explore the underlying reasons for needle and syringe sharing among PWID through ethnographic lenses in Dhaka.MethodsWe adopted peer-driven Participatory Ethnographic and Evaluation Research, entailing 6,000 h of observations at service delivery points and drug-injecting spots, 66 in-depth interviews and seven focus groups with PWID and 29 key-informant interviews with service providers, program experts and policy stakeholders. Data were thematically analyzed as per the socioecological model.ResultsThe findings presented multilayered contexts driving needle and syringe sharing. At the intrapersonal level, PWID possessed myths and misconceptions regarding needle and syringe sharing, which hindered their risk perception of needle and syringe sharing. As many PWID, especially street-based PWID, felt despondence and distress toward their life, they perceived safe injecting as futile as they were already in fatal conditions. Some PWID partook in concurrent substance use, clouding their judgment, increasing their aggression, and perpetuating risky injection. Moreover, findings showed that withdrawal took precedence in needle and syringe sharing behaviors. At the interpersonal level, PWID communities protected fraternal relationships through sharing, inherited community-bred misinformation about safe injecting practices, and were influenced by gendered and community hierarchies and power dynamics within the PWID sub-culture, which all fueled needle and syringe sharing. Shadowing sessions, observations and interviews revealed challenges at the organizational level (i.e., the PWID intervention) such as inconvenient outreach schedules in relation to PWID's drug-injecting time windows; challenges in the needle and syringe distribution approach; and a predominantly peer-focused outreach approach where peers exhibited work performance and compliance issues, and challenges in capacity building and upholding motivation among OWs. At the structural level, changes in infrastructure and associated inconveniences, criminalization of drug use and harassment of PWID, increased drug prices and financial constraints, and changes in fund allocation policy of the donor engendered risky injection.ConclusionThe findings presented multifaceted reasons for needle and syringe sharing, thus warranting multilayered interventions. It is not possible to contain needle and syringe sharing and alleviate HIV epidemics through addressing proximate causes or structural interventions alone, thus efforts need to be invested in broadening the horizons for harm reduction interventions.